Genomic landscape of head and neck cancer in Asia: A comprehensive meta-analysis of 1016 samples - Srikanth S. Manda; Nafisa Arfa; Neha Sharma; Aparna R. Parikh; Thomas J. Roberts; Sewanti Limaye; Venkataraman Ramachandran; Kumar Prabhash; Moni A. Kuriakose; Prashant Kumar (Oral Oncology Reports)
Head and neck cancer (HNC) is a diverse group of malignancies arising in the mucosal linings of the oral cavity, pharynx, and larynx, influenced by factors such as tobacco use, alcohol consumption, and human papillomavirus (HPV) infection. This study conducts a comprehensive meta-analysis of the mutational landscape of HNC across Asian cohorts, encompassing India, Korea, Japan, China, Singapore, and Saudi Arabia. The analysis highlights distinct genetic profiles influenced by environmental exposures, lifestyle habits, and genetic predispositions. Notably, the RAF family proteins, enriched in both Indian and Chinese cohorts, present potential therapeutic targets for RAF inhibitors like Vemurafenib. Additionaly, specific mutations like MET in Singaporean patients can be effectively addressed with drugs like Crizotinib, leading to rapid responses in HNSCC. Smokers exhibited high frequencies of CASP8 and FAT1 mutations. Novel driver genes, including RYR2 and ANK2, emerged with significant mutational frequencies in smokers. The RAS signaling pathway was identified as a prominent driver in HNC, contrasting with the globally prevalent PIK3CA/MTOR pathway. This study also underscores the high prevalence of HRAS mutations in Indian and Saudi cohorts. The study emphasizes the necessity for region-specific data to understand the unique molecular differences and develop effective therapies. The identification of NBEA and ANK2 as potential novel driver genes in HNC highlights new avenues for research and targeted therapeutic interventions tailored to the genetic profiles of Asian HNC patients.